A comparison of three empirical models for estimating solar radiation in Nigeria - Chineke, T.C.; Jagtap, S.S. (1995)
Using meteorological data f rom J sires in the major climatic zones of Nigeria. the solar radiation was determined from 3 empirical models that required either measured data on sunshine hours or maximum and minimum temperature. The statistical analysis revealed that. the temperature based sushine-hour equations can be used to estimate the monthly total solar radiation in Nige ria with high accuracy. An Algorithm requiring latitude in decimals of degree has been presented f or computing the daily theoretical radiation at any location.